1991
DOI: 10.1083/jcb.112.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Localization of components involved in protein transport and processing through the yeast Golgi apparatus.

Abstract: Saccharomyces cerevisiae sec7 mutants exhibit pleiotropic deficiencies in the transit of proteins through the Golgi apparatus, and elaborate an array of Golgi apparatus-like cisternae at a restrictive growth temperature (37 degrees C). The SEC7 gene encodes an essential high-molecular weight protein (227 kD) that is phosphorylated in vivo. In cell lysates, Sec7 protein (Sec7p) is recovered in both sedimentable and soluble fractions. A punctate immunofluorescent pattern of Sec7p-associated structures seen in SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
196
0
3

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(214 citation statements)
references
References 42 publications
15
196
0
3
Order By: Relevance
“…Considering that Secl2p is recycling between the ER and the cis Golgi in the wild-type yeast cells and that Rerlp is involved in proper localization of Secl2p, it would be reasonable to assume the location of the Rerlp function to be either in the ER or in the Golgi. The punctate staining pattern of strongly suggests the latter possibility; a number of Golgi proteins such as Yptlp, Sec7p, and Kex2p show punctate localization in the cytoplasm (Segev et al, 1988;Franzusoff et al, 1991;Nishikawa and Nakano, 1991;Redding et al, 1991; also see below). To support this possibility, the effect of the sec7 mutation was examined.…”
Section: Rerm Encodes a Hydrophobic Proteinmentioning
confidence: 92%
“…Considering that Secl2p is recycling between the ER and the cis Golgi in the wild-type yeast cells and that Rerlp is involved in proper localization of Secl2p, it would be reasonable to assume the location of the Rerlp function to be either in the ER or in the Golgi. The punctate staining pattern of strongly suggests the latter possibility; a number of Golgi proteins such as Yptlp, Sec7p, and Kex2p show punctate localization in the cytoplasm (Segev et al, 1988;Franzusoff et al, 1991;Nishikawa and Nakano, 1991;Redding et al, 1991; also see below). To support this possibility, the effect of the sec7 mutation was examined.…”
Section: Rerm Encodes a Hydrophobic Proteinmentioning
confidence: 92%
“…We further analyzed the relative distribution of the cisGolgi marker Anp1p-mCherry ( Figure 1B, center panel) and the Arf GEF Sec72p-GFP ( Figure 1B, left panel), a homologue of S. cerevisiae Sec7p (Franzusoff et al, 1991) that localizes to the late Golgi compartments in budding yeast. We found that these proteins localized to several punctate structures (18 Ϯ 3 cis-and 22 Ϯ 3 trans-Golgi compartments during interphase and 23 Ϯ 3 cis-and 26 Ϯ 2 trans-Golgi compartments in dividing cells, n ϭ 10 cells).…”
Section: Organization Of the Early Secretory Pathway In S Pombementioning
confidence: 99%
“…of one of the Golgi compartments, in which CaZ+-mediated protein processing [5,6] and exocytosis [7,8] take place. The Ca 2+ pumping function of Pmrlp has been suggested on the basis of sequence homology to mammalian Ca z+ pumps.…”
mentioning
confidence: 99%